IMPLEMENTATION OF INTERACTIVE LEARNING MEDIA USING POWER POINT MEDIA AND PHET ON STUDENTS' PHYSICS LEARNING OUTCOMES IN HIGH SCHOOL - Hajar Mawaddah; Khairiah Khairiah; Lia Afriyanti Nasution; Jafri Haryadi; Putri Pratiwi Lestari; Rita Destini; Putut Marwoto (JURNAL EDUSCIENCE, 2023)
The study aimed to determine of implementation and the study result of physics student’s taught by the interactive learning media using the power point and PhET interactive simulation project and study result of physics student’s taught by using the power point slides on the subject of characteristics wave in the second semester at the class XI in SMA Swasta Sinar Husni Helvetia Medan. The type of research is experimental by post-test control group design. The population in the study were all student consisting of 2 classes with amount student of 70 people. Sample in this research is the total from the population. The instrument that use to determine students learning outcomes was the result test in the  from of multiple choice questions with 24 number by 5 options of answer. The result showed that the average score of the study result of physics student’s taught by the interactive learning media using the power point and PhET interactive simulation project  that (X1) is x = 16,73 and s1 = 3,281729407, while the average score of the study result of physics student’s taught by the power point slide that (X2) is x = 14,87 and s2 = 3,135055251. Hipotesis data obtanined ttesting = 2,42 with ttable=1,997 with that mean there were a difference in the study result of the physics that significant at the implementation of the interactive learning media using the  power point and PhET interactive simulation project  for the student’s learning result of physics. Keywords : power point media, PhET interactive simulation project, result of studying physics Abstrak Penggunaan media pembelajaran dalam dunia pendidikan sangat dibutuhkan dan memiliki peran penting. Penelitian ini bertujuan untuk mengetahui implementasi serta hasil belajar fisika siswa yang diajarkan dengan media pembelajaran interaktif menggunakan  media power point dan PhET interactive simulation project dan hasil belajar fisika siswa yang diajarkan dengan menggunakan media slide power point pada pokok bahasan karakteristik gelombang kelas XI semester II di SMA Swasta Sinar Husni Helvetia Medan. Jenis penelitian yang dilakukan adalah eksperimental yang melibatkan variabel-variabel tertentu untuk menguji pengaruhnya terhadap hasil belajar fisika siswa dengan desain kelompok kontrol pos test (post-test control group design). Populasi dalam penelitian ini adalah seluruh siswa kelas XI IPA Semester II di SMA Swasta Sinar Husni Helvetia Medan yang terdiri dari 2 kelas dengan jumlah siswa 70 orang. Sampel dalam penelitian ini adalah totalitas dari populasi. Instrumen yang digunakan untuk mengetahui hasil belajar siswa adalah tes hasil belajar dalam bentuk pilihan berganda berjumlah 24 soal dengan 5 opsi jawaban. Dari hasil penelitian diperoleh nilai rata-rata hasil belajar fisika siswa yang diajarkan dengan media pembelajaran interaktif menggunakan media power point dan phet interactive simulation project (X1) adalah x = 16,73 dan s1 = 3,281729407, sedangkan nilai rata-rata hasil belajar fisika yang diajarkan dengan media slide power point (X2) adalah x = 14,87 dan s2 = 3,135055251. Uji hipotesis data diperoleh thitung = 2,42 dengan ttabel=1,997 yang berarti ada perbedaan hasil belajar fisika yang signifikan pada implementasi media pembelajaran interaktif menggunakan media power point dan PhET interactive simulation project terhadap hasil belajar fisika siswa.Kata kunci : media power point, PhET interactive simulation project, hasil belajar fisika